Análisis de las prácticas comunicativas del grupo “Coalición por la equidad de género Riobamba” en torno a la aprobación de la ordenanza N°007-2019 dentro del período enero – julio 2019 - Andrés Sebastián, Escobar Lobato (2022)
ABSTRACT: Over the years we have witnessed how the country has been developing in matters of politics, culture, economy and so on, with the influence of interesting social process that involve the active participation of certain actors, characters and collectives who have felt the need to express themselves through different forms with the aim of to promote a fairer, more equitable and sustainable citizen environment. All these forms of participation, interaction and organization allow to create within education and research area a great interest in analyzing, understanding and socialize these facts to create in this way a broad context of knowledge mainly speaking within communication. One of the important aspects to study within communication based on these facts of a social nature is precisely the analysis of communicative practices, which have to do with the investigation of all those actions that are developed within the different collectives, groups or movements, and that will be approached from the analytical methodological field and the theoretical study mainly of structuralism and the sociology of communication. Thus, the primary purpose of this research work is to analyses communicative practices that originated within a coalition where there was participation of different social groups and that in a certain way intervened in the decision making of local public policies Key words: Communicative practices, social movements, collectives, public policies, society, participation, interaction, organization.